Children as Filmmakers: Well-Being, Social Ecology, and Cognitive Mapping in Delhi at Eleven. Issue 1 (February 2022) - Stephens, John
Abstract : Delhi at Eleven, a compendium of four short films made with video cameras by eleven-year-old Indian schoolchildren in 2012, is filmed from a child's perspective – literally, in the low positioning of the single camera, and mentally, in the nature of the close attention paid to the details of events and relationships. The films create strikingly individual images of the filmmakers' world and offer sharply observed comments on the restrictions upon subjective agency and well-being in children's lives. The children were given limited training in how to make a film and completed some exercises designed to encourage them to think about the nature of a shot, framing, sequence, order, and structure. They received some mentoring in selecting footage to include and exclude. My discussion here explores the interrelationship of cognitive mapping, social ecology, and cinematic space in these films. These four films offer perspectives on urban livelihoods, marginality, class, gender, kinship, household economy, poverty, and modernity, and are thus particularly informative about how children can map their society.